Tax Incentives for High Skilled Migrants: Evidence from a Preferential Tax Scheme in the Netherlands - Lisa Marie Timm; Massimo Giuliodori; Paul Muller (Institute of Labor Economics (IZA), 2022)
This paper examines to what extent an income tax exemption affects international mobility and wages of skilled immigrants. We study a preferential tax scheme for foreigners in the Netherlands, which introduced an income threshold for eligibility in 2012 and covers a large share of the migrant income distribution. By using detailed administrative data in a difference-in-differences setup, we find that the number of migrants in the income range closely above the threshold more than doubles, whereas there is little empirical support for a decrease of migration below the threshold. Our results indicate that these effects are driven mainly by additional migration, while wage bargaining responses are fairly limited. We conclude that the preferential tax scheme is highly effective in attracting more skilled migrants.
Keywords: F22; J61; H24; H31; 330; international migration; income tax benefits; wage bargaining; bunching